Determinants of private school participation: All about the money?. (3rd March 2020) - Anders, Jake; Green, Francis; Henderson, Morag; Henseke, Golo
Abstract : For those who grew up in Britain in the latter half of the twentieth century, there is known to be a strong association between social class or family income and attending a private school. However, increasing private school fees and promotion of school choice in the state sector have potential implications for the predictors of participation in private schooling in the twenty‐first century. In this article, through analysis of rich, longitudinal data from a recent, representative birth cohort study, we provide new evidence on this issue. Given the high and rising fees required to send a child to private school, one might think that the decision is entirely connected with financial resources. However, while these remain an important factor, we argue that other determinants are also important. In particular, we highlight the importance of parental values and geographical proximity to high‐quality state school alternatives: a one standard deviation increase in levels of parental traditional values is associated with a 2.5 percentage point higher probability of their child attending a private school, while each minute of additional travel time to the nearest state school judged 'Outstanding' by England's schools inspectorate is associated with a 0.2 percentage point higher probability of attending a private school. We also examine the characteristics of those who 'mix and match' state and private schooling, noting their similarity to private school attendees in terms of their values but lower levels of financial resources.